Evaluation of left atrial and ventricular remodeling in atrial fibrillation subtype by using speckle tracking echocardiography - Lu, Shirui; Liu, Hongyun; Sun, Jie; Zhang, Jun; Li, Li; Tang, Qiaoying; Liu, Yani; Deng, Youbin (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrillation (AF) is associated with cardiac structural and functional remodeling. We investigated the left atrial (LA) and left ventricular (LV) changes in AF subtypes by using two-dimensional echocardiography strain techniques. Methods The study population consisted of 102 subjects with sinus rhythm (control group) and 463 patients with AF, among which 284 patients had paroxysmal AF (PAF) and 179 patients had persistent AF (PerAF). A speckle tracking automatic functional imaging software was used to perform the strain analysis. Results Patients with AF had dilated LA maximum and minimum volume, decreased LA reservoir strain, lower LV ejection fraction (LVEF), and impaired global longitudinal strain (GLS) compared to those of the sinus rhythm control group. In patients with PerAF, the LA maximum and minimum volumes were larger, and the LA reservoir strain [PAF vs. PerAF, 28% (21,33) vs. 19% (14, 28), P < 0.05], LVEF, and absolute GLS value (PAF vs. PerAF, −16.9 ± 3.3 vs. −14.1 ± 3.5%) were lower than those in patients with PAF. Patients with AF regardless of LA enlargement had decreased LA reservoir strain and lower LVEF and absolute GLS value than those in the sinus rhythm control group. Conclusion Compared with those with normal sinus rhythm, patients with AF had dilated LA volume and impaired LA function, which were further worsened in patients with PerAF than those in patients with PAF. LA functional impairment occurred before LA enlargement. Left atrioventricular remodeling happened across different stages of AF development.